The effects of coral transplantation and giant clam restocking on the structure of fish communities on degraded patch reefs - Cabaitan, Patrick C.
Active restoration is being practiced to supplement conservation activities for the purpose of reversing the trend of reef degradation. In the last decade, the feasibility of different restoration approaches such as coral transplantation and restocking of other marine biota were the focus of research and relatively few have examined experimentally its effects on the resultant communities. In this study, coral transplantation and giant clam restocking were applied on 25 degraded patch reefs (-25m2) inside a marine sanctuary in Pangasinan, northwestern Philippines to examine their effects on the community structure of reef fishes. Five interventions or treatments were employed; 1)"coral" consisted of transplantation of a combination of Acropora spp. and Pocillopora spp. on concrete blocks; 2)"clam" consisted of restocking of Tridacna gigas; 3)"clam+coral" consisted of restocking of T. gigas with Acropora spp.transplanted on their shells; 4)"shell" consisted of deployment of T.gigas shells; and 5)"control" consisted of no intervention. Fish communities on the patch reefs were monitored monthly for 3 months before the intervention and were monitored further for 11 months after the intervention, including 1 recruitment season. After the intervention, the coral cover and the "other biota" category increased in the coral and clam+coral treatments, respectively, due to the transplanted corals and deployed giant clams. consequently, the complexity of the substrate was enhanced. A month after the intervention, a rapid increase in the abundance and species richness of reefs fishes on the coral, clam+coral and clam treatments was observed compared to the shell and control treatments. A change in species composition of reef fish assemblage was also apparent in the coral and clam+coral treatments relative to the clam, shell and control, especially 4 months after the intervention. The present experiment demonstrates the feasibility of improving the condition of degraded patch reefs, which can subsequently enhance the fish community. Results also show the importance of the underlying substratum and the abundance of live corals and clams to reef fishes.